Understanding Indonesian E-Law and Democracy: Challenge, and Hope - Vani Wirawan (Budapest International Research and Critics University, 2022)
This study aimed to discuss how law firms quickly provide advice to citizens who need legal assistance in the digital era with the help of technology, smartphones, laptops, and computers to get justice and democracy in Indonesia. We need the data we get electronically on many complications such as journal proceedings, books, and other materials that discuss the world's understanding and development of democracy. The data we found electronically were then analyzed to understand involving a high level of evaluation and coding system to answer this research question with high principles of validity and reliability. We took several well-known publications such as application, Taylor and Francis, Google books, and some academic materials that we received technological assistance. After getting an understanding and discussion, we can briefly convey this finding, and the development of Indonesian democracy is a very significant breakthrough in an era where everyone has been able to reach information instantly through their technology with the hope that this finding will be a new solution and input for studies on the development and journey of democracy in the digital era.